PERPUSTAKAAN PERGURUAN TINGGI: PEDOMAN, PENGELOLAAN DAN STANDARISASI - Rismayeti, Rismayeti (Jurnal Ilmu Budaya, 2013)
University library is the most dominated library in Indonesia. But, some librarians don't understand about the standard of organizing library. This arcticle the function and standard of university library. It will deal with the function, service and users of university library.